2013
DOI: 10.1172/jci64551
|View full text |Cite
|
Sign up to set email alerts
|

The TGR5 receptor mediates bile acid–induced itch and analgesia

Abstract: Patients with cholestatic disease exhibit pruritus and analgesia, but the mechanisms underlying these symptoms are unknown. We report that bile acids, which are elevated in the circulation and tissues during cholestasis, cause itch and analgesia by activating the GPCR TGR5. TGR5 was detected in peptidergic neurons of mouse dorsal root ganglia and spinal cord that transmit itch and pain, and in dermal macrophages that contain opioids. Bile acids and a TGR5-selective agonist induced hyperexcitability of dorsal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
306
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 320 publications
(320 citation statements)
references
References 71 publications
4
306
1
1
Order By: Relevance
“…TGR5 is expressed in astrocytes and neurons, and is activated by neurosteroids, and functions as a neurosteroid receptor (Keitel et al, 2010). Another study showed that TGR5 may mediate bile acid-induced itch and analgesia associated with cholestasis (Alemi et al, 2013a). In this study, the investigators identified TGR5 in peptidergic neurons that transmit itch and pain in mouse dorsal root ganglia and in the spinal cord as well as in dermal macrophagecontaining opioids.…”
Section: Bile Acid Receptor Signaling In Liver Metabolismmentioning
confidence: 79%
“…TGR5 is expressed in astrocytes and neurons, and is activated by neurosteroids, and functions as a neurosteroid receptor (Keitel et al, 2010). Another study showed that TGR5 may mediate bile acid-induced itch and analgesia associated with cholestasis (Alemi et al, 2013a). In this study, the investigators identified TGR5 in peptidergic neurons that transmit itch and pain in mouse dorsal root ganglia and in the spinal cord as well as in dermal macrophagecontaining opioids.…”
Section: Bile Acid Receptor Signaling In Liver Metabolismmentioning
confidence: 79%
“…TGR5 has a wide tissue distribution, being most heavily expressed in the enteric nervous system ( 65 ); it is also present in spinal cord neurons ( 66 ) and the primary cilia of cholangiocytes ( 67 ). The consequences of this activation include release of the hormone glucagon-like peptide 1 (GLP-1), which has appetite-suppressing and antidiabetic effects ( 68 ).…”
Section: History Of Bile Acid Researchmentioning
confidence: 99%
“…Bile acids are markedly increased in the circulation and tissues of patients with cholestatic liver disease and may contribute to the chronic and intractable pruritus that is a common feature of this condition (Hayashi and Majima, 1999). TGR5 is expressed in peptidergic small diameter primary sensory neurons innervating the skin, and activation by bile acids causes a TGR5-dependent hyperexcitability and stimulates the secretion of the itch-selective transmitter gastrin releasing peptide (Alemi et al, 2013). The intradermal injection of bile acids and TGR5-selective agonists also caused robust scratching in wild-type but not tgr5 2/2 mice, whereas gainof-function transgenic mice exhibit a spontaneous pruritus.…”
Section: A the G Protein-coupled Receptor-transient Receptor Potentimentioning
confidence: 99%